BIBLIOMETRIC ANALYSIS OF FIRST LANGUAGE TRANSFER RESEARCH IN EFL CONTEXTS (2015–2025) - Siti Kharisa; Hidayat, Muhamad Taufik; Hasim, Wahid (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study presents a bibliometric analysis of research on first language (L1) transfer in English as a Foreign Language (EFL) contexts, covering publications indexed in Scopus from 2015 to 2025. Using a systematic search strategy combining terms such as L1 transfer, language transfer, first language transfer, and mother tongue interference within EFL and English writing contexts, a final dataset of 95 articles was retrieved and analyzed. The study employed VOSviewer software to construct co-authorship networks at both author and country levels, as well as keyword co-occurrence maps. Descriptive analysis was conducted using Scopus's built-in Analyze Results feature. Findings reveal a general upward trend in publication output, with a notable surge from 2022 to 2025. China emerged as the most productive country, while the Netherlands served as the primary hub of international collaboration. Six thematic clusters were identified, encompassing EFL transfer in writing contexts, error analysis and contrastive linguistics, crosslinguistic influence and L2 development, EFL writing skills and pedagogy, corpus-based L1 transfer studies, and L1 transfer among Chinese EFL learners. Keywords such as language transfer, L1 transfer, and EFL consistently dominated the field, while English writing and EFL writing contexts have emerged as increasingly prominent themes in recent years. These findings provide a comprehensive overview of the intellectual landscape of L1 transfer research in EFL contexts and offer directions for future inquiry.